Business Model Canvas for Indonesian Aerospace's CN235 Aircraft - Nurulloh, Mohamad Ikhsan; Simbolon, Luhut; Deksino, George Royke (Publisher Cv. Inara, 2022)
This research aims to conduct a qualitative assessment of the business model canvas on the CN235 Aircraft manufactured by Indonesian Aerospace (IAe). This research is a descriptive qualitative study of the business model canvas and then uses SWOT analysis to evaluate each item. Interviews and documentation are the methods for data collection. This study shows that IAe's market segmentation is domestic and global markets. The company uses a digital system and delivers services that exceed the expectations of its customers. IAe is the only domestic manufacturing industry that can manufacture aircraft. The company makes money by selling planes and providing maintenance services. Building and keeping strong connections with business partners is critical in collaboration. The most common expenditures incurred by IAe are fixed and variable expenses. The study findings are supposed to reveal the IAe's strengths, weaknesses, opportunities, internal and external challenges, and innovation strategy.